Zingerone attenuates zearalenone-induced steroidogenesis impairment and apoptosis in TM3 Leydig cell line. (May 2022) - Shahidi, Maryamsadat; Moradi, Ali; Dayati, Parisa
Abstract: Zingerone 1 (Zing) is one of the bioactive compounds of ginger rhizome ( Zingiber officinale ), whose beneficial effects have been reported previously on reproductive organ complications. The current study purposed to survey probable protective impacts of Zing against Zearalenone (ZEA)-induced changes in the TM3 Leydig cell line. Exposure of TM3 cells to ZEA (25 μM) attenuates the levels of testosterone and steroidogenesis-related genes, which was reversed by 25 μM of Zing. ZEA also induced ROS generation and apoptosis in TM3 cells. Zing treatment improved the stress oxidative and apoptosis-related changes induced by ZEA in TM3 cells by modulating autophagy-related proteins and activating PI3K-AKT-mTOR and Nrf2 pathways. The findings of this study represented a theoretical basis for Zing's protective actions against ZEA toxic effects on TM3 cells. Graphical abstract: Schematic view of Zingerone inhibitory effects against zearalenone-induced toxic actions in TM3 Leydig cell line. Image 1 Highlights: Zearalenone impairs steroidogenesis in the TM3 cell line. Zearalenone induces a redox state and apoptosis in the TM3 cell line. Zingerone normalizes Zearalenone-impaired steroidogenesis in TM3 cells. Zingerone reverses Zearalenone-induced redox state and apoptosis in TM3 cells.